SISTEM PENGOLAHAN LIMBAH PADAT DAN LIMBAH CAIR SERTA ANALISIS EFLUEN PADA PABRIK PEREKAT KAYU LAPIS DI KOTA LANGSA TAHUN 2012 - Dewi Oktarini; Irnawati Marsaulina; Indra Chahaya (Lingkungan dan Kesehatan Kerja, 2012)
The solid and liquid waste treatment system and analysis of liquid waste effluent quality on plywood glue factory in Langsa city in 2012. The chemical waste that pollutes the environment is a serious problem and supplied by industrial activities such as plywood factory. Basically the waste treatment is not a difficult activities but the waste treatment requires the application of accurate waste treatment method. This research aims to study the solid and liquid waste treatment system and analysis of liquid waste effluent quality on plywood glue factory in Langsa city in 2012. This research is adescriptive survey study by using observation sheet on solid and liquid waste treatment in plywood factory and the inspection of liquid waste sampel in effluent point and waste water treatment plant influent and the recycled liquid waste. The results of observation indicates that the solid waste treatment system in plywood factory use the incineration method, reuse of urea bag. The liquid waste treatment in plywood factory uses the sendimentation and aeratoin process. The result of laboratory analysis of liquid waste effluent is : COD 51,2 ppm, Temp 27ºC, Amonia (NH3) 0,1 ppm, TSS 3,7 ppm, Phenol 0 ppm, BOD5 25,5 ppm and pH 6,9. The conclusion of this research is solid waste treatment systems on plywood glue factory yet qualified, while the liquid waste treatment system has met the terms and parameters have been standardized. The plywood glue factory recommended to make corrections to the solid waste treatment systems, but it is also immediate burning the sludge of solid waste by using incinerators. Keywords: Waste Treatment System, Effluent Quality, Solid Waste, Liquid Waste,Quality standard